2015
DOI: 10.1068/b120012p
|View full text |Cite
|
Sign up to set email alerts
|

Did Zipf Anticipate Spatial Connectivity Structures?

Abstract: An avalanche of empirical studies has addressed the validity of the rank-size rule (or Zipf's law) in a multicity context in many countries. Under which conditions (eg, sample size, spatial scale) this ‘law’ holds remains as yet largely underinvestigated, while spatial network constellations also deserve more attention. Against this background, we investigate the relationship between network connectivity and the rank-size rule (or Zipf's law) in an urban economic network constellation. In particular, we addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…A gravitational attractor is an area of attraction of trajectories whose source is the force of gravity. The theory of geographical potential is an important component of socio-economic geography (Janowski, 1908/2013; Nijkamp and Reggiani, 1988; Pumain, 1982; Reggiani and Nijkamp, 2014; Stewart, 1948; Wilson, 2009). In a previous study (Banaszak et al., 2015), the authors have demonstrated that hierarchically organized spatial systems (or CPT-like systems) display in a dynamic context a fractal structure of spatial interactions (for example, in case of cities).…”
Section: Gravitational Attractorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A gravitational attractor is an area of attraction of trajectories whose source is the force of gravity. The theory of geographical potential is an important component of socio-economic geography (Janowski, 1908/2013; Nijkamp and Reggiani, 1988; Pumain, 1982; Reggiani and Nijkamp, 2014; Stewart, 1948; Wilson, 2009). In a previous study (Banaszak et al., 2015), the authors have demonstrated that hierarchically organized spatial systems (or CPT-like systems) display in a dynamic context a fractal structure of spatial interactions (for example, in case of cities).…”
Section: Gravitational Attractorsmentioning
confidence: 99%
“…There is an avalanche of literature on the statistical-econometric mapping and testing of hierarchical regularities among spatial actors or units in a complex spatial urban or regional and industrial world (see e.g. Batty, 2013; Reggiani and Nijkamp, 2014). Thus far, much less attention has been given to the underlying complex dynamics in shaping such rank-size or hierarchical patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Mori, Nishikimi, and Smith () propose a link between industries spatial intensity and population intensity. Finally, Reggiani and Nijkamp () interpret the estimated coefficient as an indicator of economic development in terms of the urban structure, intended as a socioeconomic connected network…”
Section: Introductionmentioning
confidence: 99%
“…That said, recent work by Mori et al . () points to various possibilities for incorporating spatial elements into the rank‐size distribution, as does the study by Reggiani and Nijkamp ().…”
Section: Rank‐size Distribution and Urban Policymentioning
confidence: 87%